Implementasi Supervisi Akademik Kepala Sekolah Dalam Meningkatkan Kinerja Guru Tingkat Sekolah Dasar - Sopacuaperu, Andreas; Repelita, Tridays; Irsyad Akmal, Muhammad; Danajaya, Muhammad Amir Slamet Abdullah (Universitas Kristen Satya Wacana, 2025)
This study aims to determine the extent of the implementation of academic supervision of the principal at SD Santa Theresia Marsudirini 77 Salatiga to improve teacher teaching performance. This study uses a qualitative descriptive approach type with the subjects being the principal and teachers of SD Santa Theresia Marsudirini 77 Salatiga. Qualitative data were taken through a series of in-depth interview techniques and document studies of the implementation of academic supervision of the principal. The study results show that the implementation of academic supervision of the principal at SD Santa Theresia Marsudirini 77 Salatiga uses guidelines set by the National Education Standards Agency including planning, implementation, and follow-up of supervision. The planning stage formulates objectives and makes a schedule for the implementation of supervision. In contrast, the implementation stage focuses on administration prepared by teachers and the implementation of learning in the classroom. The findings are that some teachers are not optimal in preparing learning devices and the selection of learning models is not relevant today. Follow-up at the stage of academic supervision of the principal of SD Santa Theresia Marsudirini 77 uses a teacher self-development approach by participating in training provided by the school, the Marsudirini Foundation, and the Teacher Working Group (KKG).